The Legislative Power: 273-292 - Köbel, Szilvia (Comparative Constitutionalism in Central Europe: Analysis on Certain Central and Eastern European Countries, 2022)
In this chapter, we present the legislative branches of eight countries (Poland, Czech Republic, Slovakia, Romania, Serbia, Croatia, Slovenia and Hungary) through the following subjects: a) legislative bodies and sources of parliamentary law (laws regulating the function of the parliament, bylaws etc.); b)the authorities of parliaments; c) the officeholders of parliaments, the house president, and committees of parliaments; d)parliamentary groups; e) the legal status of officeholders (rights of the MPs, conflict of interest, immunity). The structure of the study follows the order of the above-mentioned subjects and treats them as subchapters. At the beginning of each subchapter is a short explanation of the subject, highlighting in broad terms what it wishes to showcase. The study focuses on the legislative branches of governments as the main goal of the study is to observe their legislative ecosystem and organs, powers and members.KEYWORDS: legislative bodies, branches of power, standing orders, commities, office holders, parliamentary groups.